Enhancers and barriers to uptake of male circumcision services in Northern Uganda: a qualitative study - Nanteza, Barbara M.; Makumbi, Fredrick E.; Gray, Ronald H.; Serwadda, David; Kennedy, Caitlin E. (AIDS care, 2020)
Uganda adopted voluntary medical male circumcision (VMMC) in 2010, but uptake remains disproportionately low in the Northern region despite implementing several demand creation strategies. This study explored the socio-cultural and structural enhancers and barriers to uptake of VMMC services in Gulu, a district in Northern Uganda where uptake is lowest. In September 2016, we conducted 19 focus group discussions, 9 in-depth interviews, and 11 key informant interviews with 149 total participants. Data were collected and analyzed thematically using both inductive and deductive approaches, then framed in four levels of the social ecological model. Enhancers included adequate knowledge about VMMC services, being young and single, partner involvement, peer influence, perceived increased libido after circumcision, and availability of free and high-quality VMMC services. Barriers included sexual abstinence during wound healing, penile appearance after circumcision, religion, culture, and misconceptions. Optimizing enhancers and addressing barriers could increase VMMC service uptake in northern Uganda.
Keywords: Enhancers; Barriers; Male circumcision services